Andrew Johnson papers - Johnson, Andrew, 1808-1875.; Moore, William G. (William George), 1829-1898.
Correspondence, memoranda, diaries, messages and speeches, courts-martial and amnesty records, financial records, lists, newspaper clippings, printed matter, scrapbooks, photographs, and other papers relating chiefly to Johnson's presidency. Subjects include the Civil War, National Union Party, Republican Party, Abraham Lincoln's presidency and assassination, Reconstruction, and Johnson's impeachment. Documents Johnson's service as military governor of Tennessee (1862-1865) and his business affairs including his tailor shop in Greeneville, Tenn. Also includes diaries kept by Johnson's secretary, William G. Moore.
Correspondents include Ethan A. Allen, George Bancroft, Edward Bates, Henry Ward Beecher, James Gordon Bennett, John Milton Binckley, James B. Bingham, Jeremiah S. Black, Francis Preston Blair, Thomas H. Caldwell, Simon Cameron, Lewis D. Campbell, Salmon P. Chase, Samuel Sullivan Cox, John A. Dix, Thomas Ewing, James A. Garfield, Ulysses S. Grant, Horace Greeley, H.W. Halleck, Winfield Scott Hancock, J.C.G. Kennedy, Abraham Lincoln, John A. McClernand, Hugh McCulloch, George Gordon Meade, William G. Moore, G.W. Morgan, J.S. Negley, John M. Palmer, John Pope, Fitz-John Porter, Alexander Williams Randall, William S. Rosecrans, John McAllister Schofield, William Henry Seward, William T. Sherman, Edwin McMasters Stanton, Alexander Hamilton Stephens, Richard Taylor, Benjamin Cummings Truman, Julia Gardiner Tyler, John Williams, and Jonathan Worth.
Microfilm edition of Series 1-20 available
Microfilm produced from originals in the Manuscript Division.
Library of Congress Geography and Map Division.
U.S. president, vice president, senator, representative, and army officer from Tennessee.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Allen, Ethan A. -- Correspondence; Bancroft, George, -- 1800-1891 -- Correspondence; Bates, Edward, -- 1793-1869 -- Correspondence; Beecher, Henry Ward, -- 1813-1887 -- Correspondence; Bennett, James Gordon, -- 1795-1872 -- Correspondence; Binckley, John Milton -- Correspondence; Bingham, James B. -- Correspondence; Black, Jeremiah S. -- 1810-1883 -- Correspondence; Blair, Francis Preston, -- 1791-1876 -- Correspondence; Caldwell, Thomas H. -- Correspondence; Cameron, Simon, -- 1799-1889 -- Correspondence; Campbell, Lewis D. -- 1811-1882 -- Correspondence; Chase, Salmon P. -- 1808-1873 -- Correspondence; Cox, Samuel Sullivan, -- 1824-1889 -- Correspondence; Dix, John A. -- 1798-1879 -- Correspondence; Ewing, Thomas, -- 1789-1871 -- Correspondence; Garfield, James A. -- 1831-1881 -- Correspondence; Grant, Ulysses S. -- 1822-1885 -- Correspondence; Greeley, Horace, -- 1811-1872 -- Correspondence; Halleck, H. W. -- 1815-1872 -- Correspondence; Hancock, Winfield Scott, -- 1824-1886 -- Correspondence; Johnson, Andrew, -- 1808-1875 -- Impeachment; Kennedy, J. C. G. -- 1813-1887 -- Correspondence; Lincoln, Abraham, -- 1809-1865.; Lincoln, Abraham, -- 1809-1865 -- Correspondence; Lincoln, Abraham, -- 1809-1865 -- Assassination; McClernand, John A. -- 1812-1900 -- Correspondence; McCulloch, Hugh, -- 1808-1895 -- Correspondence; Meade, George Gordon, -- 1815-1872 -- Correspondence; Moore, William G. -- 1829-1898 -- Correspondence; Morgan, G. W. -- 1820-1893 -- Correspondence; Negley, J. S. -- 1826-1901 -- Correspondence; Palmer, John M. -- 1817-1900 -- Correspondence; Pope, John, -- 1822-1892 -- Correspondence; Porter, Fitz-John, -- 1822-1901 -- Correspondence; Randall, Alexander Williams, -- 1819-1872 -- Correspondence; Rosecrans, William S. -- 1819-1898 -- Correspondence; Schofield, John McAllister, -- 1831-1906 -- Correspondence; Seward, William Henry, -- 1801-1872 -- Correspondence; Sherman, William T. -- 1820-1891 -- Correspondence; Stanton, Edwin McMasters, -- 1814-1869 -- Correspondence; Stephens, Alexander Hamilton, -- 1812-1883 -- Correspondence; Taylor, Richard, -- 1826-1879 -- Correspondence; Truman, Benjamin Cummings, -- 1835-1916 -- Correspondence; Tyler, Julia Gardiner, -- 1820-1889 -- Correspondence; Williams, John, -- 1778-1837 -- Correspondence; Worth, Jonathan, -- 1802-1869 -- Correspondence; National Union Party (U.S. : 1864-1868); Republican Party (U.S. : 1854- ); Military government -- Tennessee; Tailors -- Tennessee -- Greeneville; Tennessee -- History -- Civil War, 1861-1865; Tennessee -- Politics and government -- To 1865.; United States -- History -- Civil War, 1861-1865.; United States -- Politics and government -- 1861-1865.; United States -- Politics and government -- 1865-1869.; Legislators -- Tennessee; Presidents -- United States; Representatives, U.S. Congress -- Tennessee; Senators, U.S. Congress -- Tennessee